Happines at Pesantren: Qualitative Studies on Salafiyah Traditional Islamic Boarding School Student - Muslikah Muslikah; DYP Sugiharto; Sugiyo Sugiyo; Anwar Sutoyo (Universitas Negeri Semarang, 2024)
Initial investigations revealed that the typical student experiences a diminished level of well-being. This research aims to delve into the happiness patterns among students, scrutinize the underlying factors, and ascertain methods for enhancing their happiness. Employing a phenomenological qualitative approach, the study elucidates that students perceive happiness subjectively. Additionally, it explores the determinants influencing student happiness and strategies for augmenting their well-being within the Islamic boarding school environment. Happiness is interpreted by students at the salafiyah/traditional Islamic boarding school as a feeling filled with togetherness, simplicity and oriented towards achieving the goals of the world and the hereafter. Factors that support the happiness of students from within are acceptance, openness, calmness, resilience, self-control and good time management. While the determinants of the happiness of students who come from the first environment are attachment and parental support, peer support and support from pesantren through kyai/ustadz. The article can significantly contribute to our understanding of students' lives in Salafiyah traditional Islamic boarding schools and has practical implications for enhancing the quality of education and student well-being in that context